(3cJGH CdajIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO agPg QSGdI hLjRI aj aQV GdUdGI (B...s
(3BNQgG (B:s
(3hdG JbVi GdLeYI hGdYjOGf(B... (3JeJ GdQSGdI GdCdajI HYhf Gddg hMSf Jhajbgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B109s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B559s
(3GdCYdGe(B: (3L(B7(3, U(B109s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis